Design and evaluation of a multihoming-based mobility management scheme to support inter technology handoff in PNEMO - Islam, Shayla; Khalifa, Othman Omran; Hassan Abdalla Hashim, Aisha; Hasan, Mohammad Kamrul; Razzaque, Md. Abdur; Pandey, Biswajeet (Springer, 2020)
Handof management is an indispensable component in supporting network mobility. The handof situation raises while the Mobile Router (MR) or Mobile Node (MN) crosses the diferent wireless communication access technologies. At the time of inter technology handof the multiple interface based MR can accomplish multihoming features such as enhanced availability, trafc load balancing with seamless fow distribution. These multihoming topographies greatly responsible reducing network delays during inter technology handof. This article proposes a multihoming based Mobility management in Proxy NEMO (MM-PNEMO) scheme that considers benefts of using multiple interfaces. To support the proposed scheme design a numerical framework is developed that will be used to assess the performance of the proposed MM-PNEMO scheme. The performance is evaluated in the state-of-art numerical simulation approach focusing the key success metrics of signalling cost and packet delivery cost, that eventually scaling the total handof cost. The numerical simulation result shows that the proposed MM-PENMO delightedly reduces the average handof cost to 60% compared to existing NEMO Basic support protocol (NEMO-BSP) and PNEMO.